POVERTY AND DEVELOPMENT IN SOUTH AFRICA’S RURAL COMMUNITIES: A SOCIOECONOMIC ANALYSIS - Pieter Johannes Botha; Nomvula Ayanda Ndlovu; Themba Vusi Zwane; Sibusiso Luthando Khumalo (International Journal of Education and Social Science Studies, 2025)
This study investigates the multidimensional character of poverty in South Africa’s rural communities and analyzes its implications for inclusive and sustainable development. The research aims to clarify how structural constraints—including limited access to education, healthcare, infrastructure, and employment—shape persistent socio-economic deprivation in selected rural provinces. Using a qualitative descriptive design, data were gathered through in-depth interviews, focus group discussions, participant observation, and document analysis. The data were examined using thematic analysis to identify recurring patterns, local dynamics, and context-specific drivers of poverty. Findings reveal not only income-based deprivation but also entrenched institutional and spatial inequalities that weaken local economic capacities and reinforce dependence on social grants. The study identifies distinctive community-led strategies—such as cooperatives, informal savings groups, and localized knowledge systems—that demonstrate resilience and offer pathways for empowerment. These insights contribute to existing scholarship by highlighting how grassroots initiatives interact with structural barriers in shaping rural development outcomes.  T The study concludes that effective rural development in South Africa requires integrated policy interventions that strengthen local capacities, enhance service delivery, and position communities as active partners in planning and implementation to reduce the rural–urban development gap.